POLITICAL PARTIES AND PARLIAMENTARY SEAT REPLACEMENT: A COMPARATIVE STUDY ACROSS FIVE DEMOCRACIES - Nurdin, Ali; Ariyan, Said; Romli, Ombi (Universitas Negeri Semarang, 2025)
The mechanism of interim replacement of parliamentarians constitutes a critical pillar of democratic representation, serving not only to ensure administrative continuity but also to reveal the extent of political parties’ influence over vacated legislative seats. This study conducts a cross-country comparative analysis of the role of political parties in interim replacement mechanisms (IRP) across five democracies: Indonesia, Singapore, Malaysia, the Philippines, and the United States. Using a qualitative comparative approach complemented by a Systematic Literature Review (SLR) of 58 scholarly works, the research examines the legal frameworks, institutional arrangements, and accountability dimensions that shape IRP. Findings demonstrate that in Indonesia and the Philippines, party elites wield dominant authority under the open-list system, frequently marginalising constituent participation and consolidating internal party power. In Malaysia and Singapore, although by-elections are formally prescribed, institutional loopholes and discretionary powers enable parties or governments to delay or circumvent these mechanisms, thereby compromising electoral legitimacy. Conversely, the United States exhibits higher levels of public participation through mandated special elections, with temporary gubernatorial appointments remaining tightly constrained. These variations underscore that the influence of political parties in IRP is highly contingent on each country’s institutional design, electoral rules, and governance norms. The study highlights the normative and practical implications of these arrangements and advocates democratic reforms that enhance transparency, institutional checks, and participatory safeguards, particularly in systems where parties retain near-absolute control. By linking institutional design to representative accountability, the article provides actionable insights for policymakers, scholars, and democracy advocates striving to foster more inclusive, transparent, and resilient legislative governance.